To your eternity. 1 - Oima, Yoshitoki (Kodansha Comics, 2017)
"An orb was cast unto the earth. After metamorphosing into a wolf, it joins a boy on his bleak journey to find his tribe. It learns and evolves, transcending death, even when those around it cannot..."--Back cover.